Properties of Instant Sourdough from Papaya (Carica papaya L.) Natural Starter and Its Effect on Bread Characteristics - Yanti, Rini; Suroto, Dian Anggraini; Manikharda, Manikharda; Putri, Yuniar Wika Perdana (Journal of Applied Agricultural Science and Technology, 2025)
Sourdough is made from water and wheat flour, fermented by lactic acid bacteria and yeast. Papaya can serve as a natural starter for producing sourdough. This study aims to assess the impact of drying on pH levels, total titratable acidity (% TTA), the viability of lactic acid bacteria (LAB), yeast viability, specific volume, and the texture profile of gluten and gluten-free bread. Three types of starters were used: P (fermented water from papaya and flour), G (fermented water from papaya, sugar, and flour), and W (mineral water and flour) to make type I sourdough (before drying). Type III sourdough (dried) was obtained using spray drying (S), cabinet drying (C), and freeze-drying (F). The pH, %TTA, LAB, and yeast viability were measured, while the specific volume and texture profiles of the breads were evaluated. Spray drying significantly affected the pH of the A sample and LAB viability in the W and G samples. Cabinet drying significantly affected the %TTA and yeast viability in the G sample. Freeze-drying significantly affected the LAB and yeast viability in the W and G samples, as well as yeast viability and %TTA in the P sample. Instant sourdough can be produced using spray, cabinet, or freeze drying and is suitable for making both gluten-containing and gluten-free bread. Variations in starter type and drying methods influence the bread's physical characteristics, including specific volume and texture profile. The drying methods significantly affected hardness, gumminess, chewiness, cohesiveness, springiness index, and resilience in both gluten-containing and gluten-free bread samples.